Determination Reference of Concentration (RfC) Xylen Exposure Based on Xylen NOAEL in White Rats and Workers’ Body Weight and Height in Surabaya Car Painting Area, Indonesia - Abdul Rohim Tualeka1 , Juliana Jalaludin2 , Prihartini Widiyanti 3, Syamsiar S Russeng4 , Pudji Rahm (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aims to calculate the value of RfC from xylen exposure around the car painting area of Surabaya, Indonesia. This is an observational cross-sectional study with quantitative data analysis methods conducted manually. The population in this study was groups of car painting workers and groups of car repairer on Jalan Pengenal Kota Surabaya. The sampling technique was proportionate stratified random sampling to take 51 people. The measurement of xylen concentration around the car painting area was 635.98 mg/m3 (146.47 ppm). This value is above the threshold value according to Minister of Manpower and Transmigration Regulation Number 13 of 2011 and Minister of Manpower Regulation Number. 5 of 2018 is 434 mg/m3 (100 ppm). RfC of car painting workers with NOAEL 50 mg/kg was 7.76 mg/kg.